2015
DOI: 10.4236/ojopm.2015.52006
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microporous Film and Microspheres Hybrids

Abstract: Hybrids consisting of a microporous film and polymeric microspheres were fabricated via a simple method without a special apparatus. Highly ordered microporous polymer films with honeycomb structure were fabricated by a dissipative process utilizing amphiphilic poly(acrylic acid)block-polystyrene, which was synthesized by atom transfer radical polymerization followed by an acid-catalyzed ester cleavage reaction. In order to embed the microsphere efficiently, the dried microporous films should be soaked in meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Generally, the interfacial tension between polymers increases as the polymer molecular weights increase, leading to morphologic changes. [43,44,45,46] Ge et al demonstrated that low molecular weight PS (L-PS) and low molecular weight PMMA (L-PMMA) form spherical Janus particles while H-PS and H-PMMA form snowman-like Janus particles. [47] The difference between the final morphologies is attributed to the different interfacial tensions between PS and PMMA with different molecular weights, i. e. the polymer/polymer interfacial tension increases as the polymer molecular weights increase, causing less interfacial area between the polymers.…”
Section: Effect Of Molecular Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the interfacial tension between polymers increases as the polymer molecular weights increase, leading to morphologic changes. [43,44,45,46] Ge et al demonstrated that low molecular weight PS (L-PS) and low molecular weight PMMA (L-PMMA) form spherical Janus particles while H-PS and H-PMMA form snowman-like Janus particles. [47] The difference between the final morphologies is attributed to the different interfacial tensions between PS and PMMA with different molecular weights, i. e. the polymer/polymer interfacial tension increases as the polymer molecular weights increase, causing less interfacial area between the polymers.…”
Section: Effect Of Molecular Weightmentioning
confidence: 99%
“…Generally, the interfacial tension between polymers increases as the polymer molecular weights increase, leading to morphologic changes [43,44,45,46] . Ge et al.…”
Section: Morphology Controlmentioning
confidence: 99%